2011
DOI: 10.3389/fnhum.2011.00167
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Continuous Flash Suppression: A New Measure of Unconscious Processing during Interocular Suppression?

Abstract: Until recently, it has been thought that under interocular suppression high-level visual processing is strongly inhibited if not abolished. With the development of continuous flash suppression (CFS), a variant of binocular rivalry, this notion has now been challenged by a number of reports showing that even high-level aspects of visual stimuli, such as familiarity, affect the time stimuli need to overcome CFS and emerge into awareness. In this “breaking continuous flash suppression” (b-CFS) paradigm, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
281
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(296 citation statements)
references
References 93 publications
12
281
3
Order By: Relevance
“…For example, they contrast with an older literature on binocular rivalry which had concluded that high-level conceptual or semantic processing was diminished for suppressed stimuli (Zimba & Blake, 1983). More recently, using CFS, Kang, Blake and Woodman (2011) found no evidence that the meanings of individual words were accessed when they were suppressed (although see Heyman and Moors, 2012, for a critique of that procedure), while Yang and Yeh (2011) found that emotionally negative Chinese words were in fact slower to break suppression than neutral words, a finding in the opposite direction to the effect found by Sklar and colleagues. 1 Recent work on statistical inference and measurement has emphasized that such inconsistent results might be expected when experiments with low statistical power are used to test for small or null effects (Gelman & Carlin, 2014), and these worries are particularly marked in this instance given concerns that data from the b-CFS method are potentially very noisy (e.g., breaking times often have a very long right tail, Moors, Stein, Wagemans, & van Ee, 2015;Stein, Hebart, & Sterzer, 2011).…”
mentioning
confidence: 99%
“…For example, they contrast with an older literature on binocular rivalry which had concluded that high-level conceptual or semantic processing was diminished for suppressed stimuli (Zimba & Blake, 1983). More recently, using CFS, Kang, Blake and Woodman (2011) found no evidence that the meanings of individual words were accessed when they were suppressed (although see Heyman and Moors, 2012, for a critique of that procedure), while Yang and Yeh (2011) found that emotionally negative Chinese words were in fact slower to break suppression than neutral words, a finding in the opposite direction to the effect found by Sklar and colleagues. 1 Recent work on statistical inference and measurement has emphasized that such inconsistent results might be expected when experiments with low statistical power are used to test for small or null effects (Gelman & Carlin, 2014), and these worries are particularly marked in this instance given concerns that data from the b-CFS method are potentially very noisy (e.g., breaking times often have a very long right tail, Moors, Stein, Wagemans, & van Ee, 2015;Stein, Hebart, & Sterzer, 2011).…”
mentioning
confidence: 99%
“…Specifically, it could be the case that attentional scope does not modulate the suppression time for faces per se, but rather accelerates feature detection, as images begin to partially emerge from CFS. To address this issue, past b-CFS studies have employed a nonrivalrous control task (Jiang et al, 2007; but see Stein, Hebart, & Sterzer, 2011; in which the stimulus-of-interest and the Mondrian are presented to both eyes. The contrast of the face image gradually increases, eventually becoming visible for detection (see Figure 1C).…”
Section: Methodsmentioning
confidence: 99%
“…In Experiment 1, our data suggested that modulation of face suppression time in b-CFS was owing to the specific attentional scope of the observers and not due to a difference in detecting visual onsets in general, evidenced by the null effect in the nonrivalrous control condition (coupled with the significant interaction). However, Stein, Hebart, and Sterzer (2011) and have recently argued that this type of control condition does not necessarily measure the same decision processes as b-CFS by showing that RT distributions are more variable for b-CFS, relative to control. Furthermore, posttest interviews reveal that most observers are able to subjectively distinguish between these two conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations